The personal is social: Four sociological approaches to nonsuicidal self‐injury. Issue 5 (17th February 2022) - Steggals, Peter; Lawler, Steph; Graham, Ruth
Abstract: Sociological interest in nonsuicidal self‐injury is over 20 years old, and the last decade shows a marked increase in journal articles and research monographs. Here, we survey and critically evaluate this growing sociology of self‐injury, providing a short history of its development, and describing the focus of four contrasting approaches used in exploring a sociology of such a private practice: institutional interactions; processes of social construal and construction; the social in the lived experience of subjects; and the role of social relations and communication. We argue that these approaches in the sociology of self‐injury more generally represent four broader social theoretical perspectives on how the personal is always‐already social. Understanding this connection between the empirical search for the social in self‐injury, and theoretical conceptualizations of the social in the personal, is key to opening up the future of the sociology of self‐injury, and appreciating what it has to offer sociology more generally. The more we understand what is social in self‐injury, the more we will understand how the personal is always‐already social; and the greater the theoretical investment in our methodological apparatus, the more we will be able to detect and comprehend the social dimension of this intensely personal practice.